Synthesis and characterization of new macrocyclic Schiff base derived from 2,6-diaminopyridine and 1,7-bis(2-formylphenyl)-1,4,7-trioxaheptane and its Cu(II), Ni(II), Pb(II), Co(III) and La(III) complexes - Ilhan, Salih; Temel, Hamdi; Yilmaz, Ismail; Sekerci, Memet (Pergamon-Elsevier Science Ltd, 2007)
A new macrocyclic ligand, 1,3,5-triaza-2,4:7,8:16,17-tribenzo-9,12,15-trioxacyclooktadeca-1,5-dien (L) was synthesized by reaction of 2,6-diaminopyridine and 1,7-bis(2-formylphenyl)-1,4,7-trioxaheptane. Then, its Cu(II), Ni(II), Pb(II), Co(III) and La(III) complexes were synthesized by template effect by reaction of 2,6-diaminopyridine and 1,7-bis(2-formylphenyl)-1,4,7-trioxaheptane and Cu(NO3)(2) (.) 3H(2)O, Ni(NO3)(2).6H(2)O, Pb(NO3)(2), Co(NO3)(2) (.) 6H(2)O, La(NO3)(3) (.) 6H(2)O, respectively. The ligand and its metal complexes have been characterized by elemental analysis, IR, H-1 and C-13 NMR, UV-Vis spectra, magnetic susceptibility, thermal gravimetric analysis, conductivity measurements, mass spectra and cyclic voltarnmetry. All complexes are diamagnetic and Cu(II) complex is binuclear. The Co(II) was oxidized to Co(III). The comparative electrochemical studies show that the nickel complex exhibited a quasi-reversible one-electron reduction process while copper and cobalt complexes gave irreversible reduction processes in DMSO solution. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: macrocyclic Schiff base; macrocyclic Schiff base complexes; 2,6-diaminopyridiiie and 1,7-bis(2-formylphenyl)-1,4,7-trioxaheptane